Right-ventricular mechanics assessed by cardiovascular magnetic resonance feature tracking in children with hypertrophic cardiomyopathy. - Joanna Petryka-Mazurkiewicz; Lidia Ziolkowska; Łukasz Mazurkiewicz; Monika Kowalczyk-Domagała; Agnieszka Boruc; Mateusz Śpiewak; Magdalena Marczak; Grażyna Brzezinska-Rajszys (PLoS ONE)
Background Although hypertrophic cardiomyopathy (HCM) is considered a disease of the left ventricle (LV), right ventricular (RV) abnormalities have also been reported on. Cardiovascular magnetic resonance feature tracking (CMR-FT) accurately and reproducibly quantifies RV myocardial deformation. Aim To investigate RV deformation disorders in childhood HCM using CMR-FT. Material and methods Consecutive subjects aged <18 years with echocardiographic evidence of HCM were enrolled. Cardiovascular magnetic resonance (CMR) was performed including RV volumetric and functional assessment, and late gadolinium enhancement (LGE) imaging. Results We included 54 children (37 males, 68.5%) with HCM, of which 28 patients (51.8%; mean extent of 2.18 ± 2.34% of LV mass) had late gadolinium enhancement. LV outflow tract obstruction (LVOTO) was detected in 19 subjects (35.2%). In patients with LVOTO, RV global longitudinal strain (RVGLS) (-16.1±5.0 vs. -20.7±5.3, p<0.01), RVGLS rate (-1.05±0.30 vs. -1.26±0.40, p = 0.03), RV radial strain (RVR) (15.8±7.7 vs. 22.1±7.0, p<0.01) and RVR rate (0.95±0.35 vs. 1.6±0.44, p<0.01) were lower than in patients without LVOTO. The RVR rate (p<0.01) was lower in patients with LGE in comparison to patients without LGE. Conclusions Children with HCM, especially with LVOTO, have significantly reduced indices of RV mechanics despite normal RV systolic function. It seems that the degree of LVOT obstruction is responsible for compromising the RV dynamics, rather than either mass or the amount of LV fibrosis.